Impact of water stress on Phaeomoniella chlamydospora abundance and Petri disease symptom development in young grapevines - Jared Hrycan; Pat Bowen; Thomas Forge; Miranda Hart; Jose Ramon Úrbez-Torres (OENO One)
Phaeomoniella chlamydospora (Pch) is one of the main pathogens causing Petri disease, a grapevine trunk disease responsible for the decline and mortality of grapevines within a few years after planting. Phaeomoniella chlamydospora has been shown to be prevalent in asymptomatic grapevine nursery material, leading to the hypothesis that it may act as a latent pathogen, transitioning from an endophytic to a pathogenic phase under grapevine stress. To investigate this hypothesis, a two-year greenhouse and a four-year field experiment were conducted on young self-rooted ‘Merlot’, and ‘Merlot’ grafted onto ‘SO4’ rootstock, artificially inoculated with different spore concentrations of Pch and subjected to water stress. Additionally, the arbuscular mycorrhizal (AM) fungus Rhizophagus irregularis was inoculated in the soil in the greenhouse experiment to investigate its effects on abiotic stress mitigation and thus, disease development in water stressed and non-stressed grapevines. DNA was extracted from the grapevine wood, and Droplet Digital™ PCR was conducted to determine Pch abundance before and after the experiments. In the greenhouse, Pch abundance in inoculated grapevines was greater in water stressed grapevines treated with AM than in stressed grapevines without AM or in non-stressed grapevines. Basal necrosis was greater in grapevines inoculated with Pch. In the field, Pch abundance was not affected by water stress, but basal necrosis was greater in grapevines inoculated with a high spore concentration of the fungus. Symptoms resembling Petri disease developed in the third year of the field experiment, where water stress increased grapevine mortality. This study shows that water stress may increase Pch abundance and mortality in young grapevines within the first few years after planting.